Transmembrane Protein ANTXR1 Regulates γ-Globin Expression by Targeting the Wnt/β-Catenin Signaling Pathway. (30th July 2022) - Jin, Tingting; Zhang, Zhaojun; Han, Yuanyuan; Li, Di; Liu, Juan; Jiang, Minmin; Zhu, Junwei; Kurita, Ryo; Nakamura, Yukio; Hu, Fangfang; Xu, Yongjie; Fang, Xiangdong; et al.
Abstract : Reactivation of fetal hemoglobin (HbF, α 2 γ 2) alleviates clinical symptoms in patients with β -thalassemia and sickle cell disease, although the regulatory mechanisms of γ -globin expression have not yet been fully elucidated. Recent studies found that interfering with the expression of the membrane protein ANTXR1 gene upregulated γ -globin levels. However, the exact mechanism by which ANTXR1 regulates γ -globin levels remains unclear. Our study showed that overexpression and knockdown of ANTXR1 in K562, cord blood CD34 +, and HUDEP-2 cells decreased and increased γ -globin expression, respectively. ANTXR1 regulates the reactivation of fetal hemoglobin (HbF, α 2 γ 2) in K562, cord blood CD34 +, and adult peripheral blood CD34 + cells through interaction with LRP6 to promote the nuclear entry of β -catenin and activate the Wnt/ β -catenin signaling pathway. The overexpression or knockdown of ANTXR1 on γ -globin and Wnt/ β -catenin signaling in K562 cells was reversed by the inhibitor XAV939 and the activator LiCl, respectively, where XAV939 inhibits the transcription of β -catenin in the Wnt pathway, but LiCl inhibits GSK3- β . We also showed that the binding ability of the rank4 site in the transcriptional regulatory region of the SOX6 gene to c-Jun was significantly increased after overexpression of ANTXR1 in K562 cells. SOX6 protein expression was increased significantly after overexpression of the c-Jun gene, indicating that the transcription factor c-Jun initiated the transcription of SOX6, thereby silencing γ -globin. Our findings may provide a new intervention target for the treatment of β -hemoglobinopathies.